Analisis Layanan Lembaga Publik terhadap Kepuasan Masyarakat di Kota Semarang - Hadi Sasana (Jurnal Ilmiah Aset, 2010)
Local governments must provide good public services, in an era of regional autonomy and fiscal decentralization.This study aimed to analyze the quality of public services to the satisfaction of the people in the city of Semarang. Analysis tool used Stuctural Equation Modeling (SEM).The results showed responsiveness and emphaty public sector had positive and significant impact on people’s satisfaction in the City of Semarang.